Lanthanum deposition from oral lanthanum carbonate in the upper gastrointestinal tract. Issue 7 (21st March 2017) - Hoda, Raza S; Sanyal, Soma; Abraham, Jerrold L; Everett, Jamie M; Hundemer, Gregory L; Yee, Eric; Lauwers, Gregory Y; Tolkoff‐Rubin, Nina; Misdraji, Joseph
Abstract : Aims: Lanthanum carbonate is used as an alternative to calcium‐based phosphate binders to manage hyperphosphataemia in patients with renal failure. The deposition of lanthanum within gastroduodenal mucosa of patients treated with the medication has been described, but given the relative novelty of this entity, the histiocytic deposits in the gastroduodenal mucosa can be confused with a variety of other processes, including infections and other drug‐induced forms of injury. Methods and results: We describe five cases of lanthanum phosphate deposition in upper gastrointestinal (GI) tract biopsies. Three cases were confirmed with scanning electron microscopy and energy dispersive X‐ray analysis, including one unique patient, status post‐renal transplant for polycystic kidney disease, who had last taken lanthanum 7 years prior to biopsy. Conclusion: Lanthanum deposition in the upper GI tract is a mimic of other drug‐related forms of GI injury, including iron pill‐related gastropathy. The key to making this diagnosis is a thorough drug history and awareness of the histological features.